After the fall : the failure of communism and the future of socialism - Blackburn, Robin; Bobbio, Norberto; Galeano, Eduardo; Gorz, André; Habermas, Jürgen; Halliday, Fred; Hobsbawm, Eric John; Jameson, Fredric; Miliband, Ralph; Molyneux, Maxine; Segal, Lynne; Thompson,Edward (London : Verso, 1991)
Bibliotheek François Vercammen
Engels
Monografie